3 - Crise économique et contre-pouvoirs au Mali - Pascal Baba F. Couloubaly (Africa Development, 1987)
The concept of world crisis, born out of the skyrocketing oil prices since 1972/73 and the economic recession which emerged in its wake has both an economic and an ideological dimension. As an economic crisis it has found expression on the African continent in an overall challenge to national development policies. However it has reached an extent which is disproportionate with explanations given that African societies are affected in a seemingly deadly and natural fashion by their inability to undertake any structural development. From an ideological point of view, the world crisis appears therefore as a cover-up of the major errors pre-dating the currant crisis. Through the doings of non-African systems, the concept itself has turned out to be more disturbing than the actual fact. Indeed the very idea of using economic facts to define social groups does not quite conceal the wish and the ability of national communities who are transcending the crisis that it is to say that they are adjusting, changing and/or counteracting the crisis. In this regard the example of the Republic of Mali is very illustrative. To be sure, Mali, an almost exclusively agricultural country which has been classified in the 1980 Report on World Development as one of the six poorest "low income countries" has made drastic structural changes. Although these changes are in the interest of the State, it is the peasantry which shoulders all the heavy burden of public expenditures. In spite of all this, however, the rural world adjusted itself and changed (through the construction of psychological and political counter powers) to the extent that it now enjoys some sort of autonomy (such as creation village associations) in a number of areas, thus demystifying the very basis of the state. As fçr the intelligentsia, its relationship with the military regime which, ftom the outset have been conflictual are presently exasperated as a result of its precarious economic plight, in addition to the conviction that no dialogue can be established with the authorities be it morally ethically or ideologically. These conflicts include student demonstrations, occupation of embassies abroad, general strike by teacher etc. Pascal Baba F. Couloubaly, Chercheur - IFAN, Cheikh Anta Diop, B.P. 206, Dakar/Sénégal.